Pelatihan Online Membuat Iklan Menarik Menggunakan Canva - Ulansari, Ramadhani; Hartanto, Soni Rudi; Setyaningrum, Leli; Suharyanto, Suharyanto; Kurahmadan, Taufik; Nurfauji, Aditya (Universitas Respati Indonesia, 2023)
Kegiatan pengabdian kepada masyarakat dengan judul